Kampanye Aktivitas Fisik dan Edukasi Gizi Seimbang pada Hari Gizi Nasional pada Masyarakat Mamuju - Hapzah Hapzah; Andi Salim; Zaki Irwan; Yudianti Yudianti; Najdah Najdah; Muhammad Hasyim; Erdiawati Arief; Nurliah Nurliah; Hernawati Hernawati; Yaya Armanugrah; Nurbaya Nurbaya (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The Basic Health Research 2018 states that one in five adults, one in five children aged 5-12 years, and one in seven adolescents aged 13-18 years are overweight or obese. This activity aims to provide nutrition education and joint exercise as a campaign to increase physical activity in the Mamuju community. This activity was carried out in two forms: exercise and nutrition consultation under individuals' nutritional problems. The activity was held on 6 February 2022. Dozens of people were actively involved in the activity. The community is enthusiastic about doing joint exercises and nutritional counseling per the nutritional problems each faces. The results of the discussion and questions and answers showed that the participants understood enough about the nutrition education that had been given. It can increase public knowledge about a balanced nutritional lifestyle, including regular physical activity. Communities must consciously and independently carry out a lifestyle of balanced nutrition and daily physical activity.